1980
DOI: 10.1042/bj1920709
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sterol biosynthesis accompanying cessation of glial cell growth in serum-free medium

Abstract: C-6 glioma cells, grown in medium supplemented with 5% delipidated foetal calf serum, were induced to enter a quiescent state by removing serum from the medium. Within 24h there was a 75-80% decline in the rate of incorporation of [(14)C]acetate or (3)H(2)O into digitonin-precipitable sterols. Experiments with [(3)H]mevalonolactone as a labelled sterol precursor suggested that the decline in sterol synthesis was regulated primarily at a point in the pathway before the formation of mevalonate. The specific acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…When the sterol-depleted cells were placed in serum-free medium without compactin for 48 h, i.e., conditions previously shown to be necessary for induction of CNP (Maltese and Volpe, 1979), the decreased cholesterol/phospholipid ratios did not change (Table 1, 48 h). This was not unexpected, because under these culture conditions cell growth ceases (Maltese et al, 1980). Thus, by prior treatment of C-6 cells for 24 h in 10% lipoprotein-poor serum with added compactin, graded sterol depletion could be produced, and the degree of sterol depletion could be maintained upon change of medium to serum-free conditions.…”
Section: Production Of Sterol Depletion In C-6 Glial Cells By Compactinmentioning
confidence: 88%
“…When the sterol-depleted cells were placed in serum-free medium without compactin for 48 h, i.e., conditions previously shown to be necessary for induction of CNP (Maltese and Volpe, 1979), the decreased cholesterol/phospholipid ratios did not change (Table 1, 48 h). This was not unexpected, because under these culture conditions cell growth ceases (Maltese et al, 1980). Thus, by prior treatment of C-6 cells for 24 h in 10% lipoprotein-poor serum with added compactin, graded sterol depletion could be produced, and the degree of sterol depletion could be maintained upon change of medium to serum-free conditions.…”
Section: Production Of Sterol Depletion In C-6 Glial Cells By Compactinmentioning
confidence: 88%
“…The activity of this enzyme is affected by agents that alter cholesterol synthesis in the livers of chickens (8) and rats (8)(9)(10). Studies in Chinese hamster ovary cells (11,12), HeLa (13), C-6 glia cells (14,15), and L-M cells (16) have also demonstrated that cholesterol biosynthesis was sensitive to changes in the HMG-CoA synthase activity.…”
mentioning
confidence: 99%
“…In the past few years compelling evidence has accumulated in the literature indicating that cell proliferation is closely linked to the synthesis of cholesterol (Chen et al, 1978: Maltese et al, 1980. As the cells reach confluency the synthesis of cholesterol diminished with concomitant decrease in the activity of HMG-CoA reductase (EC 1.1.1.34), the enzyme that under most circumstances is considered to be rate-limiting (Chen, 1981).…”
mentioning
confidence: 99%